2016
DOI: 10.1038/npp.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Allocation to a Hippocampal Engram

Abstract: The dentate gyrus (DG) is important for encoding contextual memories, but little is known about how a population of DG neurons comes to encode and support a particular memory. One possibility is that recruitment into an engram depends on a neuron's excitability. Here, we manipulated excitability by overexpressing CREB in a random population of DG neurons and examined whether this biased their recruitment to an engram supporting a contextual fear memory. To directly assess whether neurons overexpressing CREB at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 49 publications
7
128
4
2
Order By: Relevance
“…However, it remains to be determined how Silent Neurons get primed. Hypothetically, elevated CREB expression may increase the excitability and promote the priming of Silent Neurons …”
Section: Resultsmentioning
confidence: 99%
“…However, it remains to be determined how Silent Neurons get primed. Hypothetically, elevated CREB expression may increase the excitability and promote the priming of Silent Neurons …”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that relative CREB levels can affect which neurons are incorporated into a memory trace, a phenomenon referred to as memory allocation. Subsequent studies showed that inhibition of CREB-overexpressing cells negatively affects memory recall 31,3335 , and thus demonstrated the necessity of these cells for memory retrieval.…”
Section: The Role Of the Transcription Factor Creb In Memorymentioning
confidence: 99%
“…In recent years, numerous groups have developed novel strategies for visualizing and manipulating defined sets of cells that were either naturally or artificially biased to be active during memory formation or retrieval (Koya et al, 2009; Zhou et al, 2009; Liu et al, 2012; Guenthner et al, 2013; Ramirez et al, 2013, 2015; Cowansage et al, 2014; Denny et al, 2014; Redondo et al, 2014; Tanaka et al, 2014; Yiu et al, 2014; Gore et al, 2015a; Kim et al, 2015; Ryan et al, 2015; Cai et al, 2016; Okuyama et al, 2016; Park et al, 2016; Roy et al, 2016; Stefanelli et al, 2016; Trouche et al, 2016; Ye et al, 2016). After carefully considering the results of these studies, it was recently proposed that at least three conditions must be met for a set of cells to qualify as harboring, or at the very least processing, a component of an engram (Mayford, 2014; Josselyn et al, 2015; Tonegawa et al, 2015).…”
Section: Necessity and Sufficiency Are Not Necessarily Sufficientmentioning
confidence: 99%
“…For instance, in vivo electrophysiology and histological approaches have revealed sparse activity in DG cells that are exquisitely sensitive to contextual changes (Leutgeb et al, 2007; Satvat et al, 2011). In terms of necessity, lesioning or pharmacologically inactivating the DG often impacts memory encoding but does not have an impact on retrieval (Lee and Kesner, 2004); optogenetically silencing the DG has a similar effect and impairs memory encoding but not retrieval (Kheirbek et al, 2013); yet, chemo- and optogenetically inhibiting ~6%–9% of DG cells that were previously active during learning, but not a similar fraction of randomly active DG cells, impairs memory encoding and retrieval, thus unmasking the real-time necessity of putative engram cells for these stages of memory (Denny et al, 2014; Park et al, 2016). …”
Section: Necessity and Sufficiency Are Not Necessarily Sufficientmentioning
confidence: 99%
See 1 more Smart Citation